2017
DOI: 10.1080/01443615.2017.1308321
|View full text |Cite
|
Sign up to set email alerts
|

A trial of oral nifedipine and oral labetalol in preeclampsia hypertensive emergency treatment

Abstract: This observational retrospective cohort study was conducted to compare oral nifedipine and labetalol for emergency treatment of hypertension in preeclamptic patients. Time (minutes) and necessary doses were outlined to achieve blood pressure lower than 150/95 mmHg. In 14 patients with preeclampsia, 55 hypertensive emergencies were identified (BP >150/95). Of these emergencies, 43 were treated with oral nifedipine 10 mg (10 patients) and 12 with oral labetalol 100 mg (4 patients). To achieve a target blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…He observed that nifedipine use, was associated with a 7.4-mm Hg reduction (−14.4 to −0.4 mm Hg) in central aortic pressure, measured by pulse wave analysis. Jorge Duro-Gomez et al (2017) [12] did an observational retrospective cohort study, included all pregnant women diagnosed with pre-eclampsia & were treated with oral nifedipine or oral labetalol. The mean reduction of BP was 31.19/15.67mmHg for the Nifedipine group and 30.1/11mmHg for the Labetalol group which was consistent with the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He observed that nifedipine use, was associated with a 7.4-mm Hg reduction (−14.4 to −0.4 mm Hg) in central aortic pressure, measured by pulse wave analysis. Jorge Duro-Gomez et al (2017) [12] did an observational retrospective cohort study, included all pregnant women diagnosed with pre-eclampsia & were treated with oral nifedipine or oral labetalol. The mean reduction of BP was 31.19/15.67mmHg for the Nifedipine group and 30.1/11mmHg for the Labetalol group which was consistent with the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Shekhar S et al (2016) [10] No difference No difference Hangarga US et al (2016) [4] 42% 50% Thakur et al (2017) [16] LESS MORE Jorge Duro-Gomez et al (2017) [12] 75% 70% Present study 26% 44%…”
Section: Lscs Rate Labetalol Nifedipinementioning
confidence: 98%
“…En el Ecuador se recomienda el inicio de tratamiento de emergencia con Nifedipino de acción corta vía oral como fármaco de primera línea. Múltiples investigaciones avalan que no existen diferencias significativas entre el labetalol y nifedipino como droga de primera línea (Ghelfi et al, 2021); incluso este último reduce la tensión arterial de manera más rápida y de manera no menos segura que el labetalol (Duro-Gómez et al, 2017).…”
Section: Tratamientounclassified
“…After performing independent samples t-test analysis, results indicated that participants under nifedipine medication, the oral calcium channel blocker usually prescribed to treat hypertension, to prevent preeclampsia (408) or used as a tocolytic agent in women with preterm labour -as it appears to be superior to β2-adrenergic-receptor agonists and magnesium sulfate and should therefore be considered as the first-line tocolytic agent for the management of preterm labour (409) -showed a statistically significant increase in maternal cortisol levels postnatally (p<0.05 ) (Table 4. ).…”
Section: Analysis Of Postnatal Salivary Cortisol and α-Amylase Levels Based On Demographic Epidemiological Clinical Data And Psychologicamentioning
confidence: 99%
“…In the case of nifedipine, be it either used as a first-line tocolytic agent for the management of preterm labour or prescribed to treat hypertension / preeclampsia (408), it affects both blood pressure and adrenocortical responses (420). Simply put, nifedipine's use in preterm labour may allow more time for corticosteroids to improve the baby's lung function and provide time for transfer of the mother to a well-qualified medical facility before delivery.…”
Section: Medication Use and Salivary Cortisol And Salivary α-Amylase Measures Of Stressmentioning
confidence: 99%